Tecnologia IgY aplicada no imunodiagnóstico da neurocisticercose humana utilizando fração de Taenia crassiceps obtida por hidrofobicidade - Paiva, Guilherme Carrara Moreira (2019)
Human neurocysticercosis (NCC) is a worldwide neglected disease caused by the metacestode of Taenia solium and responsible for various complications and neurological disorders. The aim of this study was to use specific IgY antibodies produced by laying hens immunized with hydrophobic fraction of Taenia crassiceps metacestodes (hFTc), for application in immunodiagnosis of human NCC. Antibodies obtained from chicken egg yolk were fractionated, purified and evaluated for potential production and antigen recognition (anti-hFTc). Indirect ELISA and Western blotting assays were carried out to evaluate the kinetics of production and avidity of maturation of IgY antibodies anti-hFTc throughout the experimental activity. The purified and specific IgY antibodies anti-hFTc were applied in an indirect immunofluorescence assay for detection of parasitic antigens in histological sections of Taenia crassiceps metacestodes. Sandwich ELISA assays were performed to detect circulating immune complexes formed by IgG and parasitic antigens in human sera. A total of 114 serum samples were selected and divided into three groups: Group 1 (n = 44), composed by individuals with confirmed NCC and subdivided into active NCC (n = 22) and inactive NCC (n = 22); Group 2 (n = 35), by healthy individuals for NCC; and Group 3 (n = 35), by individuals who presented other parasitic diseases based on parasitological exams. The results revealed a diagnostic performance of 93.2 % sensitivity and 94.3 % specificity for detection of immunocomplexes in human sera with confirmed NCC. In conclusion, specific IgY antibodies produced from immunization of hens with hFTc antigens were able to detect T. solium immune complexes in human sera, being an efficient tool for NCC immunodiagnosis.